Comparing the effectiveness between Air-Q intubating laryngeal airway and ambu® auragain™ laryngeal mask for controlled ventilation in paediatric patients : a randomized controlled trial - Said, Nirawanti Mohamad (2018)
Background: Supraglottic airway device (SAD) is a common device use in anaesthesia practice including paediatric patients. Air-Q ILA (Cook gas LLC; Mercury Medical, Clearwater, FL, USA) is the newer first generation of SAD that can use for both primary airway device and an aid for tracheal intubation. Available literature demonstrated that this device performed better and equally to the other SAD including second generation of SAD. Ambu® AuraGain™ (Ambu, Ballerup, Denmark) is a newer second generation of SAD which incorporates both integrating gastric port access and intubation capability. The study is conducted to compare the effectiveness between Air- Q and Ambu AuraGain for controlled ventilation in children up to 30kg. Methods: 64 paediatric patients underwent various short surgical procedures were randomly assigned to receive either an Air-Q or Ambu AuraGain. Fibreoptic (FO) grades of laryngeal view were measured as the primary outcome. The secondary outcomes measured were oropharyngeal leak pressure (OLP), number of attempts, time of successful insertion, quality of airway during placement and maintenance of anaesthesia, haemodynamic parameters and complications. Results: Air-Q has more favourable FO grades of view compared to the Ambu AuraGain (P = 0.047). OLP is significantly higher in Air-Q group compared to Ambu AuraGain (19.41 ± 1.19 cm H20 vs 17.56 ± 1.52 cm H20, P value = <0.001). There were no differences in term of number of attempts, time of successful insertion, quality of airway during placement and maintenance of anaesthesia and complications.